The Derivation of Triconsonantal Weak Verbal Nouns in Modern Standard Arabic: A Nonlinear Phonological Analysis (Global Journal of Human-Social Science, 2022)
The present study analyzes the phonological processes that verbal nouns VNs undergo in the course of their derivation from triconsonantal weak verbal stems in Modern Standard Arabic MSA The VNs that are targeted in the study comprise all the instances of VNs which are listed under triconsonantal weak verbs in the corpus-based dictionary mu c d am allu ah al c arabijjah almu c a sirah Dictionary of Modern Arabic Language The 1222 targeted VNs are arranged into tables in accordance with their 35 morphological patterns and the X-slot and the feature geometry models of nonlinear phonology are utilized for analyzing their derivation from their verbal stems One of the main findings of the study is that forming VNs from triconsonantal weak verbs follow a regular derivational pattern which involves applying the ablaut and metathesis rules to their verbal stems and the addition of specific affixes to them This finding enables refuting the general hypothesis that deriving VNs from triconsonantal weak verbs is irregular in the sense that various morphological patterns and no specific rules are employed for their derivation
Keywords: nonlinear phonology; MSA; VNS; weak stems; corpus-study